1957
DOI: 10.2136/sssaj1957.03615995002100020002x
|View full text |Cite
|
Sign up to set email alerts
|

Subsoil Conditions and Their Effects on Oxygen Supply and the Growth of Corn Roots1

Abstract: The effects of subsoil density, fertility, and moisture content on soil aeration and root growth are reported. A factorial experiment having two levels each of subsoil compaction, fertility, and moisture was conducted.Oxygen diffusion rates in the subsoil were studied by two methods. Oxidation-reduction potentials were determined.Corn roots did not penetrate a subsoil compacted to a bulk density of 1.5 g. per cc., but they grew profusely in subsoil with a bulk density of 1.2 g. per cc.Quantitative information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

1965
1965
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 0 publications
2
23
0
3
Order By: Relevance
“…Bertrand and Kohnke (1957) and Deepagoda et al (2011) reported that the gas diffusivity threshold limiting plant root gaseous exchange is 0.02 under field conditions. Bertrand and Kohnke (1957) and Deepagoda et al (2011) reported that the gas diffusivity threshold limiting plant root gaseous exchange is 0.02 under field conditions.…”
Section: Soil Gas Storage and Exchangementioning
confidence: 99%
“…Bertrand and Kohnke (1957) and Deepagoda et al (2011) reported that the gas diffusivity threshold limiting plant root gaseous exchange is 0.02 under field conditions. Bertrand and Kohnke (1957) and Deepagoda et al (2011) reported that the gas diffusivity threshold limiting plant root gaseous exchange is 0.02 under field conditions.…”
Section: Soil Gas Storage and Exchangementioning
confidence: 99%
“…Soil compaction by grazing animals has been demonstrated in many studies (Lodge 1954;Orr 1960;Reed and Peterson 1961;Gifford et al 1977;Watkin and Clements 1978;Wood and Blackburn 1984;Davies et al 1989;Naeth et al 1990). It is known that high soil compaction may limit crop yield because of its adverse effects on root growth, soil water and air movement, and the water and air-holding capacity of soil (Bertrand and Kohnke 1957;Smith and Restall 1971;Jaggi et al 1972).From the literature cited above, it can be concluded that pastureland cannot maintain its initial productivity or plant species composition if poorly managed. The traditional practice to rejuvenate pasture/hayland in central Alberta has been to break the land by plow and re-seed.…”
mentioning
confidence: 99%
“…Compaction can adversely affect growth and penetration of roots into the soil and soil aeration (Bertrand and Kohnke, 1957;Jaggi et al, 1972). Mechanical impedance was probably the major factor which reduced the development and extension of roots into the subsoil in this study.…”
Section: Discussionmentioning
confidence: 99%